Integration between information and documentation management official (PPID) and legal documentation and information network (JDIH) in state university public body to realize public information openness - Koko Srimulyo; Sabrie, Hilda Yunita; Martha Kusumawardhani; Faizal Kurniawan (Technium Social Sciences Journal, 2024)
One of the duties of the State University (PTN) Public Body is to establish an Information and Documentation Management Official (PPID) as stipulated in Law Number 14 of 2008. The objective is to secure the right of citizens to know public policy planning, public policy programs, the process of public decision-making, reasons for making decisions, as well as documentation about its legal products. On the other hand, the Legal Documentation and Information Network (JDIH) is regulated in Presidential Regulation Number 33 of 2012. One of its functions is to ensure the establishment of a unified and integrated system for managing legal documentation and information across various government agencies and other institutions. In carrying out their functions, PPID and JDIH of state universities with a legal entity (PTN-BH) often experience conflicts of interest in terms of human resources and scope, which causes the ineffective performance of PPID and JDIH of PTN-BH. Therefore, it is essential to harmonize the execution of their duties to optimize the objectives of establishing PPID and JDIH, specifically to achieve transparency in public information. This research uses a qualitative research methodology which refers to descriptive research analytics. The data was collected through observation, interviews, documentation, literature studies, and statutory regulations and then analyzed through data reduction techniques, data presentation, and verification/conclusion.